1995
DOI: 10.1089/hyb.1995.14.167
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antiidiotypic Antibody ACA 125 Mimicking the Tumor-Associated Antigen CA 125 for Immunotherapy of Ovarian Cancer

Abstract: A new concept of oncological immunotherapy comprises the attempt to trigger the immune system of the host into a response against tumor cells. Antiidiotypic antibodies bearing the internal image of an antigen expressed on the surface of the tumor seem to be most suited for this purpose. We have generated a murine antiidiotypic antibody (ACA 125) functionally imitating the tumor-associated antigen CA 125, which can be detected in about 80% of ovarian carcinomas. The hybridoma cell was adapted to serum-free medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In vitro CDC as well as ADCC was observed by ACA 125, but further investigations in vivo Concentrations of MT201 and rituximab tested are indicated. Data are from a FACS-based cytotoxicity assay are necessary for determination of its efficacy (Schlebusch et al 1995). M0v18 is a chimeric monoclonal that binds the membrane folate receptor expressed on ovarian carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro CDC as well as ADCC was observed by ACA 125, but further investigations in vivo Concentrations of MT201 and rituximab tested are indicated. Data are from a FACS-based cytotoxicity assay are necessary for determination of its efficacy (Schlebusch et al 1995). M0v18 is a chimeric monoclonal that binds the membrane folate receptor expressed on ovarian carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody functionally imitates the CA125 antigen and induces humoral as well as cellular anti-CA125 immunity in animals (21,22) and humans (16,18,23). A clinical Phase I study in patients with recurrent ovarian carcinoma showed that 67% of the patients developed specific anti-anti-Id antibody (Ab3) directed against the vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies of Wagner, Anti-anti-Id antibodies (Ab 3 ) that bind to ACA125 (Ab 2 ) and CA125(Ab 1 ) were produced by application ACA125 to immune epithelial ovarian cancer or recurrences. (18)(19)(20)(21) Forty-two patients with platinum-pretreated recurrences were included in a clinical Phase I/II trial of consolidation in third-line therapy. The survival of the whole ACA125-treated collective of patients after a mean of 12.6 antibody applications was 14.9 6 12.9 months.…”
Section: Discussionmentioning
confidence: 99%